2018
DOI: 10.1177/0284185118762613
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MRI detection of atherosclerosis in ApoE-deficient mice by using tenascin-C-targeted USPIO

Abstract: Tenascin-C expression increased with the progression of atherosclerosis. Anti-tenascin-C-USPIO could provide a useful molecular imaging tool for detecting and monitoring atherosclerotic plaques by MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The degree of decline is related to the local iron accumulation (1921). Here, 24 h after administration was selected as the optimal imaging time, and signal decline is usually seen within 24 h after administration (22,23). The signal decrease was detected at the lesion site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of decline is related to the local iron accumulation (1921). Here, 24 h after administration was selected as the optimal imaging time, and signal decline is usually seen within 24 h after administration (22,23). The signal decrease was detected at the lesion site.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic plaque formation was dynamically viewed at different times (10,16,22, and 28 weeks). The morphology of aorta plaques was observed by optical microscope (Nikon, Japan) on hematoxylin and eosin (H&E) staining and immunohistochemical staining.…”
Section: Induction Of Atherosclerosis In Apoe-knockout Micementioning
confidence: 99%
“…A further study demonstrated that tenascin-C, a multifunctional extracellular glycoprotein that is highly expressed in advanced atherosclerotic plaques and is associated with inflammatory changes and plaque rupture, can serve as a marker for atherosclerotic plaques [ 187 ]. After injection of anti-tenascin C-ultra-small IONPs, MR images correlated well with histopathological analysis and the progression of atherosclerotic plaques.…”
Section: Cardiovascular Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…For instance, intravascular ultrasound and optical coherence tomography [ 10 , 11 , 12 , 13 ] provide information on plaque morphology but are invasive procedures. Other non-invasive imaging strategies might offer new opportunities for atheroma diagnosis [ 14 , 15 ], particularly magnetic resonance imaging (MRI), which combines excellent soft-tissue contrast, good resolution, and absence of exposure to ionizing radiation [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%